Internalising corporate social responsibility (CSR) –looking beyond directors’ duties - Mohd. Sulaiman, Aiman @ Nariman (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
There is an increasing interest on the issue of corporate responsibility and what is the role of corporate law and directors’ duties in ensuring companies adopt responsible business practices. This article reviews the reasons why focusing on director’s duties provisions to ensure that corporations adopt and implement socially responsible business practices is inadequate. This article uses the asbestos compensation claim in Australia as an example of the inadequacies of the directors’ duties provision. It also suggests what external factors must be in place to achieve CSR within the corporate legal framework without the drastic change of codifying directors’ duties to stakeholders.